Pathology of cornea in cattle and buffaloes - SRAVANTHI, A K; PARMAR, N S (The Indian Journal of Animal Sciences, 2013)
Cattle (650) and buffaloes (1 842) were screened for ocular lesions. Those showing lesions (56 cattle and 166 buffuloes) were subjected to histopathohlgical studies. Pathological abnormalities were observed in the cornea of 27 cattle and 51 Buffuloes. The lesions encountered were oedema, vascularization, degeneration, inflammation, ulceration, pigmentation and neoplasia.